The effect of flaxseed extraction on skin elasticity of the healing wound in rabbit - Abdul Jabbar, Omar; Kashmola, Muhanad Ali Hamdon; Mustafa Al-Ahmad, Basma Ezzat; Mokhtar@Makhtar, Khairani Idah; Muhammad, Siti Aeshah @ Naznin; Abdul Rahim, Roslina (2018)
Medicinal herbs are widely used because of low side effects, recommendation of related industries for cultivation of medicinal plants, preventing the outflow of currency, and particularly the suggestion of world Health Organization to use medicinal herbs. On the other hand, due to lack of an effective medicine for wound healing studying the effects of medicinal herbs on wound healing is essential. Management of disturbed wounds, large skin defects and the areas where skin tension precludes wound closure is of high clinical importance. Healing in such wounds occurs through epithelization and contraction processes (second-intentions healing) that may result in certain undesirable complications including keloid formations, poor final cosmetic appearance and the formation of a fragile epithelial